2018
DOI: 10.1111/josl.12310
|View full text |Cite
|
Sign up to set email alerts
|

‘I don't come off as timid anymore’: Real‐time change in early adulthood against the backdrop of the community

Abstract: The period from ages 18 to 25 is sometimes called ‘emerging adulthood’ (Arnett , ) since it has come to be characterized by major life transitions. Linguistically, this means that lifespan change in the individual (Sankoff , ) might be particularly likely during these years (Labov : 447; Bigham : 533; Kohn : 20). Addressing a need for more real‐time sociolinguistic research on early adulthood, we employ data from a panel study of a single speaker, ‘Clara’ (b. 1986), interviewed every 12 to 18 months between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 49 publications
(114 reference statements)
0
3
0
Order By: Relevance
“…Third, Arnett (2000) characterizes emerging adulthood (i.e., the period between ages 18 and 25 years) as a time of feeling in-between adolescence and adulthood, experiencing cognitive and affective instability, and exploring one’s identity. Some emerging adults may also be undergoing a sociolinguistically formative point in their lives in which they are learning to use their voices instead of defaulting to their previous patterns of timidity (Brook, Jankowski, Konnelly, & Tagliamonte, 2018). Applied to this study, disengaged-joking communicators may be starting to form their identity as adults by voicing their amusement about what it means to grow older through teasing others about age and playing along when their own age is the subject of jokes.…”
Section: Discussionmentioning
confidence: 99%
“…Third, Arnett (2000) characterizes emerging adulthood (i.e., the period between ages 18 and 25 years) as a time of feeling in-between adolescence and adulthood, experiencing cognitive and affective instability, and exploring one’s identity. Some emerging adults may also be undergoing a sociolinguistically formative point in their lives in which they are learning to use their voices instead of defaulting to their previous patterns of timidity (Brook, Jankowski, Konnelly, & Tagliamonte, 2018). Applied to this study, disengaged-joking communicators may be starting to form their identity as adults by voicing their amusement about what it means to grow older through teasing others about age and playing along when their own age is the subject of jokes.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of decade of birth, against the reference value of the 1910s, the only decade with a proportion of who that differs significantly is the 1990s: the youngest people in the corpus use significantly more who than the oldest people, while none of the other decades is statistically distinguishable from the people born in the 1910s. The possibility of age-grading away from the standard in young adulthood, who, cannot be ruled out; Brook et al (2018) found this in a panel study of a young woman in Toronto. However, the sex effect and educational effect suggest a role for change in progress with an acceleration occurring recently in apparent time.…”
Section: Statistical Modelingmentioning
confidence: 99%
“…5) se documenta que en el español de la Ciudad de México de los años 1970 y 2000 los grupos de mayor edad siempre presentan un mayor volumen de léxico sustantivo. Cambios en la estructura gramatical a lo largo de la vida se discuten en Brook et al (2018).…”
Section: Mayoresunclassified